A 3.4 dB NF k‐band LNA with a tapped capacitor matching network in 65 nm CMOS technology. Issue 2 (18th September 2014) - Xu, Jianfei; Yan, Na; Zeng, Xiaoyang; Gao, Jianjun; Yang, Chen
ABSTRACT This article proposes a tapped capacitor network for low‐noise amplifier (LNA) input matching which can provide much broader bandwidth than traditional ones. According to the design, the implemented LNA can realize noise match and power match simultaneously, which will broaden LNA's bandwidth without introducing larger noise than traditional ones. In addition, input pad parasitic capacitance can be absorbed by the network. Then a k‐band LNA with the matching network designed in 65 nm CMOS technology is shown to demonstrate the performance of the matching network. The tested results show that frequency band of S11 less than −10 dB is about 17 GHz and minimum NF is about 3.4 dB. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:146–153, 2015.